RETRACTED: The Influence of Democratic Leadership Style, Intrinsic Motivation and Work Discipline on Employees’ Performance at PT. Pangansari Utama Food Industry, East Jakarta - Elsa Nopitasari; Herry Krisnandi; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
The aim of this research is to analyze how much influence democratic leadership style, intrinsic motivation and work discipline have on individual employee performance. This research was conducted at PT. Pangansari Utama Food Industry East Jakarta. This research data uses primary data in the form of a questionnaire to 100 respondents at PT. Pangansari Utama Food Industry using the multiple linear regression method which was processed using SPSS 17.0 software. The research results show in partial testing the influence of democratic leadership style, intrinsic motivation and work discipline on employee performance. Between Democratic Leadership Style (X1), Intrinsic Motivation (X2) and Work Discipline (X3) on Employee Performance (Y) shows a positive and significant influence. This shows that the three independent variables, namely democratic leadership style, intrinsic motivation and work discipline have influenced Y. The determination test result is 0.608, this shows that the variables democratic leadership style, intrinsic motivation and work discipline contribute 60.8% to the employees’ performance of PT Pangansari Utama Food Industry. This shows that there are still other factors that account for 39.2% of employee performance. The magnitude of this influence is PT. Pangansari Utama Food Industry East Jakarta must pay more attention to democratic leadership style, intrinsic motivation and work discipline to improve the employees’ performance of PT. Pangansari Utama Food Industry East Jakarta.